A busca ativa de estudantes (in)visíveis: a palavra dos professores na perspectiva de uma educação inclusiva. - Santos, Regenilson Veras (2023)
This dissertation is the result of the research we developed in the master’s course in Language Sciences, in the research line Processes of Linguistic Organization and Social Identity to obtain the master's degree. The intention of the work is to analyze the strategies used by basic education teachers in the classroom with the student with Attention Deficit Hyperactivity Disorder (ADHD) seeking to understand inclusive education through the expression that considers inclusive linguistics, as a right of all to individuality. Imbued with a systemic look at the various facets of Brazilian education, a heterogeneous education, the teacher and his training, the neuroatypical student, the person with ADHD, considered included in the basic training spaces, represents what we seek to develop. The theoretical basis was based on the works of Barkley, Teixeira; Lagares, Martelotta, Glat, Mazzotta, Mantoan, Figueiredo, among others, having as main pillar the conceptions of Vygotsky on language, learning and participation in the society of people with disabilities who must reflect on the praxis of being a teacher in the presence of inclusive linguistics in the teaching and learning process in an equally inclusive perspective. Gardou, Gnerre and Rohde are also basic to understand the educational process in the same perspective of inclusion and ADHD. As applied methodology, the approach was qualitative, with analysis of the corpus consisting of reports of interviews with semi-structured questions answered by nine (09) high school teachers, in addition to the records of observations of classes taught in an inclusive school in the city of Recife. At the end of this work, we better understand the school and social occurrences that surround the context in which they were described, making it possible to adopt a broad inclusive action, improving the quality of the development of those who participated in this investigation. We also realize that the inclusion process for the student with ADHD still needs an action of all actors for this process to happen in a real and concrete way.